Investigation of MIM Diodes for RF Applications - Khan, Adnan (2015)
Metal Insulator Metal (MIM) diodes that work on fast mechanism of tunneling have been used in a number of very high frequency applications such as (Infra-Red) IR detectors and optical Rectennas for energy harvesting. Their ability to operate under zero bias condition as well as the possibility of realizing them through printing makes them attractive for (Radio Frequency) RF applications. However, MIM diodes have not been explored much for RF applications. One reason preventing their widespread RF use is the requirement of a very thin oxide layer essential for the tunneling operation that requires sophisticated nano-fabrication processes. Another issue is that the reliability and stable performance of MIM diodes is highly dependent on the surface roughness of the metallic electrodes. Finally, comprehensive RF characterization has not been performed for MIM diodes reported in the literature, particularly from the perspective of their integration with antennas as well as their rectification abilities. In this thesis, various metal deposition methods such as sputtering, electron beam evaporation, and Atomic Layer Deposition (ALD) are compared in pursuit of achieving low surface roughness. It is worth mentioning here that MIM diodes realized through ALD method have been presented for the first time in this thesis. Amorphous metal alloy have also been investigated in terms of their low surface roughness. Zinc-oxide has been investigated for its suitability as a thin dielectric layer for MIM diodes. Finally, comprehensive RF characterization of MIM diodes has been performed in two ways: 1) by standard S-parameter methods, and 2) by investigating their rectification ability under zero bias operation. It is concluded from the Atomic Force Microscopy (AFM) imaging that surface roughness as low as sub 1 nm can be achieved reliably from crystalline metals such as copper and platinum. This value is comparable to surface roughness achieved from amorphous alloys, which are non-crystalline structures and have orders of magnitude lower conductivities. Relatively lower resistances of the order of 1 k ohm with a sensitivity of 1.5 V-1 have been obtained through DC testing of these devices. Finally, RF characterization reveals that input impedances in the range of 300 Ω to 25 Ω can be achieved in the low GHz frequencies (from 1-10 GHz). From the rectification measurements at zero bias, a DC voltage of 4.7 mV has been obtained from an incoming RF signal of 0.4 W at 2.45 GHz, which indicates the suitability of these diodes for RF rectenna devices without providing any bias. It is believed that with further optimization, these devices can play an important role in RF energy harvesting without the need to bias them.